Leaching of nitrate nitrogen into the groundwater after clear felling and site preparation - Kubin, E. (Boreal Environment Research Publishing Board, 2024)
The concentration of nitrate nitrogen in the groundwater was investigated one year before and during ten years after clear felling, collecting of logging residues and ploughing that took place in 1986 at the Pahalouhi and Hautala experimental sites at Kivesvaara, located in the middle boreal coniferous forest zone in the central part of Finland (64°28´N, 27°33´E). All the treatments caused a rise in nitrate nitrogen concentrations at both sites. Having been initially virtually zero, the concentrations of nitrate nitrogen continued to rise for 5–7 years, reaching 500–700 ug l–1 at their highest, after which they began to decrease. Concentrations were still high ten years after the treatments, a situation which has not been found earlier.